Correlation of Physical-Chemical Parameters to Total Coliform Value in Jawi River, Pontianak, West Kalimantan - Rahmawati Rahmawati; Laili Fitria; Liza Syafitri (Biosaintifika: Journal of Biology & Biology Education, 2017)
Coliform bacteria can be used as an indicator of the presence of pathogenic bacteria, such as E.coli bacteria that cause diarrhea. The aimed of this study is to determine the relationship between physical-chemical parameters namely temperature, pH, DO and BOD to the density of coliform bacteria in Jawi River, Pontianak. The sampling was conducted at one point each in the upstream, midstream and downstream area of the Jawi River during two tidal conditions of the Kapuas River in September 2016 at 09:40 (at low tide) and at 15:40 (at high tide). The correlation of physical-chemical parameter to coliform value was tested Pearson Product Moment. The results showed that coliform bacterial density increased from upstream to downstream with 150-1500 MPN/100 ml at high tide and 930-11000 MPN/100 ml at low tide. The results showed that the coliform bacterial density value had a positive relation with pH and BOD parameters and negative relation with temperature and DO parameters. So, it can be concluded that there is a correlation between physical parameters, such as temperature and chemical parameters such as pH, DO and BOD to microbiological parameters especially Coliform bacterial density. The benefit of this study is to give information about water quality of Jawi River and its correlation with density of Coliform bacterial, so that people are expected to pay more attention to the use of clean water to avoid the disease caused by coliform.